Karakteristik Ibu Hamil dengan Kekurangan Energi Kronis (KEK) Sebagai Dasar Penguatan Intervensi Gizi Maternal di Desa Sukamulya - Silvia Widyani Heriyanti; Ratna Suminar; Siti Rohmah; Yudita Ingga Hindiarti (Universitas Galuh, 2026)
Chronic Energy Deficiency (CED) among pregnant women is a public health problem that increases the risk of low birth weight, prematurity, and maternal and neonatal morbidity and mortality. In Ciamis Regency, the prevalence of CED among pregnant women has shown an increasing trend. Sukamulya Village was selected as the study setting due to the continued occurrence of CED cases despite the availability of basic maternal health services, indicating the need for a community-based assessment. This study aimed to describe the characteristics of pregnant women with CED in Sukamulya Village, Ciamis Regency. This study employed a descriptive survey design. The study population consisted of all pregnant women with CED in Sukamulya Village, totaling 25 respondents, using total sampling. Data were collected through a structured questionnaire and analyzed descriptively using frequency and percentage distributions. Most respondents had primary school education (36%), were aged 20–35 years (44%), were primigravida (64%), and were unemployed (56%). Pregnant women with CED in Sukamulya Village were generally within the healthy reproductive age range but were predominantly characterized by low educational level, primigravida status, and unemployment. These findings provide practical implications for health workers, particularly midwives, to strengthen nutritional education, improve early antenatal care services, and optimize targeted and sustainable supplementary feeding programs.